Obesity and dyslipidemia: risk factors for development of senile cataract - Azim, Sabrina Fahmida; Akhter, Qazi Shamima; Akter, Taslima; Farid, Fouzia (Journal of Bangladesh Society of Physiologist, 2018)
Background: Cataract is a major cause of blindness and visual impairment worldwide.Obesity and dyslipidemia may act as risk factors for development and progression of senile cataract. Objective: To determine obesity and dyslipidemia as the risk factors for development of senile cataract. Methods: This case control study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2014 to June 2015. For this study, 100 diagnosed senile cataract patients (DSC) of both sexes, aged 41-70 years, were selected by purposive sampling as study group from Department of Ophthalmology, Dhaka Medical College and one hundred noncataract healthy adult subjects (NCG) were recruited as control among the relatives and hospital staff through personal contact.The criteria for inclusions are BMI e” 25.0 kg/m² ,waist circumstances > 88 cm in female and >102 cm in male and waist hip circumference ratio W: H > 0.85 infemale and > in male 0.9.Person with cataract due to trauma, acute or chronic diarrhoea, kidney disease, history of taking calcium channel blockers, lipid lowering agents and steroid were excluded from this study. For assessing lipid profile TC, TAG, HDLC, LDL-C of all subjects were estimated by enzymatic method. For statistical analyses, unpaired Student’s ‘t’ test, and logistic regression were done to evaluate the risk factors. Odds ratios (OR) with 95% Confidence Intervals (CI) were provided. Results: In this study BMI, WC, W: H, TC, TAG, LDLC levels were significantly higher (P<0.001)and HDL-C level was significantly lower (P<0.001) in diagnosed senile cataract patients(DSC) as compared to non-cataract group(NCG). Conclusion: From the study results, it is concluded that obesity (higher BMI, WC,W: H) and dyslipidemia may act as risk factors for development of senile cataract. J Bangladesh Soc Physiol. 2018, June; 13(1): 29-34